Safety and efficacy of plasma exchange treatment in children with AQP4-IgG positive neuromyelitis optica spectrum disorder - Li, Zhichao; Wan, Lin; Liu, Xinting; Wang, Jing; Shi, Xiuyu; Zhou, Huanfen; Xu, Quangang; Wei, Shihui; Yang, Guang (Frontiers in Immunology, 2023)
Neuromyelitis optica spectrum disorder (NMOSD), a severe demyelinating disease, is rare among children. Plasma exchange (PE) is widely used as a salvage therapy for severe and corticosteroid-unresponsive patients with NMOSD. Presently, there are limited studies on the safety and efficacy of PE in children with NMOSD. Herein, we report the case of six children with NMOSD who received PE along with the outcomes and adverse events. All six children (female, age at onset 4 years 9 months–13 years 2 months) were AQP4-IgG positive and received standard PE using the COM.TEC Cell Separator. The interval between NMOSD onset and PE was 29 days (range 10–98). Only one patient (P3) who received PE 10 days after acute exacerbations exhibited clinical improvement. Her left visual acuity increased from 0.06 to 0.6 (spectacle-corrected visual acuity was 1.0) and her EDSS score decreased from 4 to 3 points. The other five patients had no clinical improvement and no EDSS scores changes after PE. Adverse events included rashes (P1, P3), acute non-occlusive thrombosis of the internal jugular vein (P1), and thrombocytopenia (P2). In conclusion, the timing of PE initiation as a rescue therapy for severe and corticosteroid-unresponsive pediatric AQP4-IgG positive NMOSD may be crucial to treatment efficacy, and early initiation of PE may be associated with a better outcome. Furthermore, PE has the potential risk for clinically significant adverse effects that should be considered before initiating the therapy and should be weighed against potential benefits.